Socioeconomic, Environmental, and Behavioral Determinants of Leprosy in Kediri, East Java - Anindita Hasniati Rahmah; Ruben Dharmawan; Setyo Sri Rahardjo (Masters Program in Public Health, 2018)
Background: Leprosy remains a major public health problem in the world, particularly in developing countries. Leprosy can be so progressive that damages skin, nerve, extremity, and eye organs of the affected patients. Cumulative incidence of leprosy amounted to 200,000 cases worldwide, with the highest incidences occuring in India, Brazil, and Indonesia. This study sought to examine the social economic, environmental, and behavioral determinants of leprosy in Kediri, East Java, using path analysis approach.Subjects and Method: This was an analytic observational study with case control design. The study was conducted at Leprosy Hospital, Kediri, East Java, from November to December 2017. A total sample of 150 study subjects consisting of 75 leprosy patients and 75 non-diseased subjects were selected for this study by fixed disease sampling. The dependent variable was leprosy. The independent variables were personal hygiene, education, employment status, family income, dwelling density, humidity, and migration. Data on leprosy diagnosis was taken from medical record. The other data were collected by questionnaire. The data were analyzed by path analysis.Results: The risk of leprosy increased with poorer personal hygiene (b= -1.20; 95% CI= -1.92 to -0.49; p=0.001), higher humidity (b= 0.73; 95% CI= 0.33 to 1.43; p=0.040), and migration (b= 0.94; 95% CI= 0.14 to 1.74; p= 0.022). Being employed status increased family income (b= 1.41; 95% CI= 0.72 to 2.11; p< 0.001). Low family income increased the likelihood of migration (b= -14; 95% CI= -1.71 to -3.19; p= 0.007) and dwelling density (b= -1.02; 95% CI= -1.71 to -0.32; p=0.004). Higher education level increased the likelihood of being employed (b= 1.41; 95% CI= 0.72 to 2.11; p< 0.001) and better personal hygiene (b= 1.15; 95% CI= 0.44 to 1.85; p= 0.001). Dwelling density increased the likelihood of humidity (b= 4.29; 95% CI= 3.22 to 5.37; p< 0.001).Conclusion: Migration, higher humidity, and poorer personal hygiene directly increase the risk of leprosy. Education, employment status, family income, and dwelling density indirectly affect the risk of leprosy. Keywords: Leprosy, social economic, environmental, personal hygieneCorrespondence: Anindita Hasniati Rahmah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: aninditarahma22@gmail.com.Journal of Epidemiology and Public Health (2018), 3(2): 253-262https://doi.org/10.26911/jepublichealth.2018.03.02.05